In Vivo Platelet Release in Myeloproliferative Disorders - Ireland, H; Lane, D A; Wolff, S; Foadi, M (Thrombosis and Haemostasis, 1982)
The in vivo platelet release reaction in 22 patients with myeloproliferative disorders has been studied by measuring plasma concentrations of the platelet release product β-throm-boglobulin (βTG). Mean βTG and mean βTG:whole blood platelet count ratio were significantly raised in the patient group taken as a whole compared to an age matched control group. No significant increases were observed in the plasma concentrations of thrombin and plasmin sensitive fibrinogen fragments fibrinopeptide A (FpA) and Bβ1-42. The patients were divided into those who had normal, increased or decreased responses to in vitro ADP-induced platelet aggregation. Mean βTG and the mean βTG:whole blood platelet count ratio were higher in the increased and decreased responders to ADP than in the normal aggregation group, but the differences in means were not statistically significant. Aspirin given to six patients at a dose sufficient to eliminate the secondary phase of ADP-induced platelet aggregation reduced mean βTG and the mean βTG : whole blood platelet count ratio but did not alter mean FpA and Bβ1-42. It is concluded that the enhanced platelet release reaction seen in myeloproliferative disorders is independent of plasma protease activity that arises when coagulation and fibrinolytic systems are activated.
Keywords: Myeloproliferative disorders; βTG; FpA; Bβ1-42